Persepsi Siswa Non Muslim Terhadap Pendidikan Agama Islam di Sekolah Menengah Pertama (SMP) Yayasan Pendidikan Islam (YPI) Tunas Bangsa Palembang - Hidayat Hidayat (El-Idare, 2019)
This article is titled non-Muslim students' perceptions of Islamic religious education in the Tunas Bangsa Palembang Islamic Education Foundation (YPI) Middle School. Perception is the activity of the human soul in recognizing stimuli or stimuli obtained through sensory devices with the ability of humans to be able to interpret and recognize their environment, so perceptions vary according to their respective environments. This article uses descriptive analysis, a population of 29 students. data collection techniques through interviews, documentation, observation and questionnaires. The data analysis technique is quantitative analysis to find out the data of non-Muslim students' perceptions of Islamic religious education by analytically describing its implementation using a percentage model. So it can be concluded that the perception of non-Muslim students towards Islamic education in general has shown a good perception, this can be seen in the results of a questionnaire that has been given to all non-Muslim students, amounting to 29 students in YPI Tunas Bangsa Palembang Junior High School.